A high‐quality, homogenized, global, long‐term (1993–2008) DORIS precipitable water data set for climate monitoring and model verification. Issue 12 (24th June 2014) - Bock, Olivier; Willis, Pascal; Wang, Junhong; Mears, Carl
Abstract For the first time a high‐quality, consistent, global, long‐term data set of zenith tropospheric delay (ZTD) and precipitable water (PW) is produced from Doppler orbitography radiopositioning integrated by satellite (DORIS) measurements at 81 sites. The data set was screened using a two‐level procedure. First, postprocessing information is used to apply range checks and outlier checks to ZTD and formal error estimates. Second, outliers are detected by comparing DORIS ZTD with European Centre for Medium‐Range Weather Forecasts reanalysis (ERA‐Interim) data. These procedures reject 3% and 1% of the data, respectively. A linear drift is evidenced in the screened DORIS ZTD data compared to ERA‐Interim and Global Positioning System (GPS) data, which potentially results from biases introduced by the progressive replacement of Alcatel antennas with Starec antennas. The DORIS PW is homogenized by applying a bias correction computed form comparison with ERA‐Interim data each time station equipment is changed. The homogenized DORIS data are in excellent agreement with GPS data (correlation of 0.98 and standard deviation of differences of 1.5 kg m−2) and with ERA‐Interim and satellite PW data (correlation > 0.95 and standard deviation of differences < 2.7 kg m−2). The agreement with radiosonde data is less good. Preliminary results of water vapor trends and variability are shown for 31 sites with more than 10 years of data. Good consistency is found between DORIS PW trends and ERA‐Interim trends, which demonstrates the high potential of the DORIS PW data set for climate monitoring and model verification. The final DORIS PW data set is freely available in the supporting information.